An open-source power balance model for the estimation of tokamak net electrical power output - Petrov, Alexander; Stroud, Tom; Blackburn, Daniel; Owoeye, Taiwo; Wray, Steven; Zarebski, Kristian; Acres, Jack; Abdallah, Mohamad; Clements, Chris; Cannon, Marius; Christie, Finlay; Jackson, Timothy; et al. (Fusion engineering and design, 2023)
One of the largest hurdles for commercialisation of magnetic confinement fusion has historically been achieving net power — existing experiments require more electricity to keep the tokamak running than it could theoretically generate, and none have been equipped with thermal to electric conversion equipment. When designing a machine that intends to overcome this, there must be a cheap and robust way for the designer to estimate what the net power will be, preferably with the ability to perform parametric sweeps, without having to know the detailed design of each system. The work presented in this paper is an integrated time-dependent model, describing the power demands of the major tokamak components (magnets, cryogenics, heating and current drive, etc.), as well as the power generated, with a focus on the steady-state operation. The physics are implemented in OpenModelica and make use of a Python API (Application Programming Interface) to collect inputs, run studies and record outputs. The model cannot be validated against real world data, since there is no operational tokamak in the world designed for electrical power generation. Therefore, the correctness of each submodule (i.e., the magnet model, the cryogenics model) has been validated either from first principles or via validation against data from JET (Joint European Torus) where possible. The model has been used extensively as part of the work on the UK’s Spherical Tokamak for Energy Production (STEP) and has informed decisions on the STEP concept. It is publicly available on GitHub. •Multi-system power consumption and generation.•Python API with OpenModelica back-end.•Open-source code.